2023
DOI: 10.32388/fo1cp6.3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

OpenAI ChatGPT Generated Content and Similarity Index: A study of selected terms from the Library & Information Science (LIS)

Abstract: With the increasing popularity of OpenAI ChatGPT there are concerns about its use and abuse from all over the globe. Few have appreciated this effort and others are skeptical about it. Whether a proponent or opponent of this tool, no one can deny the fact that this new Artificial Intelligence (AI) tool will revolutionize every aspect of human being. In this context, the ChatGPT contents generated through OpenAI ChatGPT are analyzed with the selected terminologies of Library and Information Science (LIS) discip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This provides children with the most advanced way of cheating school assignments, and it is currently unclear whether or not AI use is detectable by traditional plagiarism software. One study has noted that ChatGPT can paraphrase texts and reduce plagiarism levels significantly but still display a plagiarism rate that would be suspicious to teachers (45%) [22]. However, another study found that ChatGPT responses only had 13% similarity on Turnitin.com -a plagiarism detection softwarewhen generating responses to prompts [23].…”
Section: Chatgptmentioning
confidence: 99%
“…This provides children with the most advanced way of cheating school assignments, and it is currently unclear whether or not AI use is detectable by traditional plagiarism software. One study has noted that ChatGPT can paraphrase texts and reduce plagiarism levels significantly but still display a plagiarism rate that would be suspicious to teachers (45%) [22]. However, another study found that ChatGPT responses only had 13% similarity on Turnitin.com -a plagiarism detection softwarewhen generating responses to prompts [23].…”
Section: Chatgptmentioning
confidence: 99%
“…AI-generated content (AIGC) engages models trained on vast text or document chunks providing content closely related to the prompts supplied by its user [58,59]. Conversational LLMs, such as ChatGPT, extract outputs of related contents of patterns and structures similar to prompts given by a user in a process known as prompt engineering [60]. ChatGPTcreated by OpenAI has generated a high similarity index of text and documents as natural language responses to questions and statements asked by its users [59][60][61].…”
Section: Information Extraction As Text Generationmentioning
confidence: 99%
“…Conversational LLMs, such as ChatGPT, extract outputs of related contents of patterns and structures similar to prompts given by a user in a process known as prompt engineering [60]. ChatGPTcreated by OpenAI has generated a high similarity index of text and documents as natural language responses to questions and statements asked by its users [59][60][61]. Te use of ChatGPT to generate fake content is debatable but its applied use for educational materials cannot be overemphasized.…”
Section: Information Extraction As Text Generationmentioning
confidence: 99%
“…In the LIS field, there has been a growing body of research focusing on the theoretical aspects related to models akin to ChatGPT. For instance, some studies have delved into the technical ethics and risks associated with ChatGPT-like models [4][5][6], and others have explored how to better harness ChatGPT in LIS [7,8]. However, these studies have primarily centered on the theoretical influences and application analyses of ChatGPT without conducting extensive practical experiments or testing within actual LIS scenarios.…”
Section: Introductionmentioning
confidence: 99%